2012
DOI: 10.1155/2012/492803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endocrine Profile andIn VitroFertilization Outcome in Patients with PCOS, Ovulatory PCO, or Normal Ovaries

Abstract: Aim. To compare the basic endocrine profile and outcomes of in vitro fertilization (IVF) in women with polycystic ovary syndrome (PCOS), ovulatory polycystic ovaries (PCO), or normal ovaries (NO). Methods. The basic clinical features and in vitro fertilization and embryo transfer outcome in patients receiving IVF or intracytoplasmic sperm injection (ICSI) were retrospectively analyzed. Results. The body mass index, basal luteinizing hormone, and testosterone levels were significantly lower in patients with ovu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
(40 reference statements)
6
15
2
Order By: Relevance
“…These results suggest for the first time that the down-regulation of aromatase in PCOS may be a result of the hyperandrogenic follicular environment. Consistent with previous studies (Dickerson et al 2010, de Resende et al 2010, Nejad et al 2011, Zhong et al 2012), the present study has shown that PCOS women have similar fertilization rates, good embryo quality rates and clinical pregnancy rates in ART as compared to non-PCOS women (Table 4). A possible reason for this might be that the pituitary suppression treatment necessary for ART have overcome the high LH level in PCOS (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest for the first time that the down-regulation of aromatase in PCOS may be a result of the hyperandrogenic follicular environment. Consistent with previous studies (Dickerson et al 2010, de Resende et al 2010, Nejad et al 2011, Zhong et al 2012), the present study has shown that PCOS women have similar fertilization rates, good embryo quality rates and clinical pregnancy rates in ART as compared to non-PCOS women (Table 4). A possible reason for this might be that the pituitary suppression treatment necessary for ART have overcome the high LH level in PCOS (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the actual incidence rate of moderate to severe OHSS was significantly higher in the PCOS group (11.5 %) compared to the controls (4.9 %). Such findings are all in line with those reported by others [11,12,14,15]. There was also a trend of higher rate of moderate to severe OHSS in the isolated PCO group (8.2 %) which corresponded to a 67 % risk increment compared to the controls although not reaching statistical significance.…”
Section: Discussionsupporting
confidence: 92%
“…This echoed the findings in some reported studies [10,[12][13][14][15], while some others have reported higher pregnancy rates in women with PCO compared to controls [9,11]. In contrast to some of the reported studies, our study made use of age-matched controls, which eliminated the confounding effect of age to the treatment outcome.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations